MARXISM AND OIL LITERATURE CHARACTERISTICS IN ABDURRAHMAN MUNIF’S CITIES OF SALT - Al-Shraah, Sameer M. (European Scientific Journal, ESJ, 2015)
Cities of Salt can be studied as a manifestation of Marx’s interpretation of colonialism and economy. Marxism here is used as a mirror that reflects the real faces of the colonizer and the capitalists who uses oil to exploit the Bedouins, their environment, and the workers. Thus, this research argues that studying Cities of Salt from a Marxist and an oil literature point of view helps in unveiling the dilemmas associated with this discovery of oil in the Bedouins’ land to the world. This makes this literary work a possible provider of proper solutions to the exploitation which the colonized people and their environment suffers as a result of this oil discovery in their land.